Հովհաննես Քռնեցու քերականական երկի սահմանումների լատիներեն նախօրինակները - Սիրունյան, Տիգրան («Նաիրի» հրատ.)
Some of Hovhannes Krnetsi‟s grammatical definitions, which significantly differ from the approach inherited from the Hellenizing grammars (the Armenian version of Dionysius Thrax and its Armenian commentaries), were formerly presented as authorial commentary. Our study revealed that the originality attributed to Krnetsi has been exaggerated; the examined sections are literal translations or paraphrases from the Institutiones Grammaticae of the Latin grammarian Priscian. Additions by the author are rare and non-essential. Some passages can be traced back to other Latin and Armenian sources. The parallels drawn with the Latin text allow us to specify the terms calked from Latin and offer some corrections to the text of the critical edition. Ряд грамматических определений Ованнеса Крнеци существенно отличается от подходов, унаследованных от грекофильских грамматик (перевода Дионисия Фракийского и eго армянских комментаторов). В предисловии к изданию текста они интерпретированы как самостоятельные комментарии. В настоящем исследовании показано, что приписываемая автору грамматики самостоятельность преувеличена: упомянутые определения являются дословными переводами или пересказами выдержек из труда Institutiones grammaticae латинского грамматика Присциана. Aвторские вкрапления малочисленны и не представляют собой существенного дополнения к сочинению. В некоторых случаях возможно указать на другие латинские и армянские источники. Латинские параллели позволяют определить термины, скалькированные с латинского, а также предложить ряд исправлений в тексте критического издания памятника.
Keywords: Բանասիրություն